The Bioremediation Potential Of Eisenia Fetida And Eudrilus Eugeniae In Cadmium And Copper Polluted Cow Dung: Bioremediation Potential of Earthworms in Heavy Metal-Polluted Cow Dung - Khan, Md Imran; Kashem, Md Abul; Aziz, Md Abdul (Journal of the Sylhet Agricultural University, 2025)
An experiment was conducted from March to November 2024 at the vermicompost shed and laboratory of the Department of Soil Science, Sylhet Agricultural University, to see the bioremediation potential of earthworms through vermicomposting from cow dung. Two factors, where A- Two earthworm species viz., Eisenia fetida and Eudrilus eugeniae; and B- cadmium and copper concentrations viz., control (natural presence of Cd and Cu in cow dung), Cd (0.15 mg kg-1), Cu (5 mg kg-1), Cd+Cu (0.15+5, mg kg-1), were employed completely randomized design (CRD) with three replications. Twenty-five earthworms were released into 500 g of cow dung in each bowl. The moisture level of cow dung was maintained between 60-80%. Data were recorded on the number of earthworms, cocoons, hatchlings, length, biomass, cadmium and copper contents in the earthworm’s body. The vermicompost weight, its physical and chemical properties changes were also recorded. The result showed that the vermicompost was dark brown, ammonia off-odour, non-granular and not sticky. The highest number of earthworms, cocoons and hatchlings, was 26.83, 41.83 and 88.17 bowl-1 found in control, respectively. Earthworm length (9.78 cm), biomass (12.32 g bowl-1), and vermicompost weight (282.74 g bowl-1) were the highest in control. The highest concentrations of Cd and Cu (0.068 and 4.694 mg kg-1, respectively) were found in the earthworm’s body in Cd+Cu (0.15+5, mg kg-1) treatment, whereas the lowest Cd (0.133 mg kg-1) and Cu (6.565 mg kg-1) were recorded in the vermicompost of control. E. fetida and E. eugeniae showed statistically similar performance in case of the Cd and Cu accumulated in their bodies. The result indicated that earthworms would reduce Cd and Cu contents from cow dung and keep the environment clean from hazardous materials. J. Sylhet Agril. Univ. 12(1): 1-15, 2025